MANDIBULAR FILLING: CASE REPORT - Raquel de Oliveira Marques Feitosa, Ana; Regina Veronezi, Lauscea; Vivianne Nogueira, Márcia; Rabelo Lima Barbosa, Chrystianne; Rodrigues Ribeiro, Henrique; Lemos Maia, Juliana; Elayne Silva Montezuma, Gina; Januzzi Santos, Marcelo (Health and Society, 2023)
Context: Mandibular contouring is important for facial appearance and maintaining youth, as well as being key to defining masculine versus feminine facial features. Dermal fillers, for the most part, are non-invasive and temporary procedures, and may be a choice for correcting mild to moderate lack of definition in the mandibular contour of individuals who seek a less invasive treatment when compared to surgery or who have not yet decided to make permanent changes. in your facial appearance. Objective: To evaluate the effectiveness of the highly crosslinked hyaluronic acid-based filler, Restylane@LyftTM, for treating the mandibular line using the MD Codes technique. Methods: A brief literature review on jaw augmentation using injectable fillers, as well as a case report. Results: Observed through a quantitative evaluation method, obtained through stereophotogrammetry with the Vectra software, quantified through a metric scale of motion vectors and a metric scale of relief observed during treatment. Conclusions: There is high efficacy in the use of highly crosslinked hyaluronic acid filler, Restylane@LyftTM, using the MD Codes technique for volumization and redefinition of the mandibular contour.